Microwave Drying Method before Sieving to Obtain Accuracy of Sand Size Parameters - Patricia Lopez-Garcia; Juan J. Muñoz-Perez; Antonio Contreras-de-Villar; Francisco Contreras-de-Villar; Jeanette Romero-Cozar; Pilar Diaz-Carrasco; Bismarck Jigena-Antelo (Journal of Marine Science and Engineering, 2024)
The purpose of this study is to determine the differences between the size parameter findings, comparing the results of a muffle during a 12-h sand-drying process with those of a microwave, because the effectiveness of sand drying with a microwave has not previously been studied. To achieve the best outcomes and assess any inaccuracies, a technique was established. Several power levels and durations were used in the tests. Furthermore, as the median particle size (D50) affects the porosity of sand, samples from three beaches in the south of Spain with varying sand sizes were used in this study. When drying for at least 5 min, the error findings for D50 are less than 3.5%, which is perfectly acceptable for beach nourishment purposes. Regarding power, 462 watts was the optimal power; a lower power, approximately 300 watts, did not completely dry the material, even after nearly 15 min. Furthermore, errors in the sorting (σ) parameter were negligible. It is essential to implement the following recommendations in microwave drying methods: the use of a light and wide container for the sand, interruptions during drying, and a minimum duration of 5 min.